2016
DOI: 10.1080/21568316.2015.1137968
|View full text |Cite
|
Sign up to set email alerts
|

On the demand for agritourism: a cursory review of methodologies and practice

Abstract: During the last decades agritourism has expanded tremendously worldwide givenvisitors'increased interest to appreciate the life in the countryside and farmers' need to enhance their revenuesfrom different economic activities. Despite such enlarged agritourism development, scant information is available on the state of its demand at both national and international levels.Given such a need, we cursory reviewed the range of econometric methods employed to evaluate the demand of agritourism, summarizing the salien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 33 publications
3
38
0
2
Order By: Relevance
“…A plausible reason could be that the demand for agritourism is higher for higher population density areas like cities and suburban areas. Our finding is consistent with Santeramo and Barbieri (), Bernardo et al . (), and McGehee and Kim ().…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…A plausible reason could be that the demand for agritourism is higher for higher population density areas like cities and suburban areas. Our finding is consistent with Santeramo and Barbieri (), Bernardo et al . (), and McGehee and Kim ().…”
Section: Resultssupporting
confidence: 94%
“…We also found that compared to farms located in a rural area, those located in an urban and suburban area are more likely to engage in agritourism. This finding is consistent with Santeramo and Barbieri (), Bernardo et al . () and McGehee and Kim ().…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…So far, research on agritourism has mainly focused on demand and supply analyzed as separate components. According to Santeramo and Barbieri (), further research is needed to investigate the characteristics of demand while controlling for different types of settings, motivations, and tourism flows (e.g., local and international tourists). So far, only a few studies have analyzed the demand characteristics of agritourism (e.g., Carpio, Wohlgenant, & Boonsaeng, ; Gao, Barbieri, & Valdivia, ; Melstrom & Murphy, ; Ohe & Ciani, ; Santeramo & Morelli, , Santeramo, ; Santeramo & Morelli, ), whereas the majority of the studies have focused on the supply side, and in particular on the characteristics of agritourism firms (Ammirato & Felicetti, , ; Barbieri, ; Barbieri, Mahoney, & Butler, ), motivations of providers (Barbieri, ; LaPan & Barbieri, ), and agritourism performance (Barbieri & Mshenga, ; Mastronardi, Giaccio, Giannelli, & Scardera, ; Pulina, Dettori, & Paba, ).…”
Section: Introductionmentioning
confidence: 99%